Enhancing Students Reading Comprehension in Recount Text through Cooperative Learning Model of IX Grade SMP Negeri 1 Siantar - Juliana Tifani; Tiodor Sihotang; Sarah Lumbantobing; Ariel Jonivedi Silalahi; Dumaris E Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This research, entitled “Enhancing Students’ Reading Comprehension in Recount Text through Cooperative Learning Model (Jigsaw) of IX Grade SMP Negeri 1 Siantar,” aimed to determine whether the Jigsaw technique could improve students’ comprehension of recount texts. The problem of this study was based on the students’ difficulty in identifying main ideas, finding detailed information, and understanding the structure of recount texts. To address this issue, the Cooperative Learning Model through the Jigsaw technique was applied to encourage active participation and peer collaboration during the learning process. This study employed a descriptive quantitative design and involved 32 students of class IX-5 at SMP Negeri 1 Siantar in the academic year 2025/2026. The data were collected through a reading comprehension test consisting of 20 multiple-choice questions conducted in one meeting. The results showed that students’ comprehension improved significantly after learning through the Jigsaw technique. The total pre-test score was 1,970 with a mean of 61.56 (Fair), and the post-test score increased to 2,560 with a mean of 80.00 (Good), showing an improvement of 30.02%. The findings indicate that the Jigsaw technique effectively enhanced students’ ability to identify main ideas, recognize text organization, and interpret vocabulary in context. Therefore, it can be concluded that the Cooperative Learning Model using the Jigsaw technique is an effective and engaging strategy for improving students’ reading comprehension in recount texts Keyword : Jigsaw technique, cooperative learning, reading comprehension, recount text, junior high school